HPV-p16 as Major Etiological Agent in Causation of Oral Squamous Cell Carcinoma - Brupta, Mankita (Journal of Contemporary Medical Practice, 2026)
According to recent WHO 2020 statastics Oral cancers ranked as 13th most common cancer worldwide. The global incidence of cancers of the lip and oral cavity is estimated to be 3, 77, 713 new cases and 1, 77, 757 deaths in 2020. [1] Oral cancer is more common in men and in older people, more deadly in men compared to women and it varies strongly by socio-economic circumstances and it is 20 per 100000 population that makes 30% of overall cacers in India. [1]Multiple studies have been published stating tobacco and betel nut chewing, smoking, alcohol consumption as major etiological factor in causation of Oral squamous cell carcinoma (OSCC). This is multifactorial from which we focussed on our aim to establish Human Papilloma Virus (HPV)-p16 as one of the major etiological agent in the causation of OSCC. Hence this study includes three hierarchial molecular marker p16-a molecular marker for HPV, Epidermal Growth Factor Receptor (EGFR) as pathway activator, and Ki67 as cellular proliferation factor. [2] This observational study included 78 cases of both biopsies and resection specimens and studied various other parameters like age, gender, presentation of lesion, site distribution, histomorphological spectrum and complete TNM staging and stage grouping for 31 resection cases. All mentioned parameters are then correlated with the so said IHC markers-p16, EGFR and Ki67 and results were analyzed and concluded.